Respuesta :
Answer:
3
Step-by-step explanation:
Put the given numbers in the formula and do the arithmetic.
f(2) = -2·f(1) = -2·(-1.5) = 3
The next term of the sequence is 3.
Answer: 3.
Step-by-step explanation:
Given : A sequence is defined recursively by the formula [tex]f(n + 1) = -2f(n)[/tex]
The first term of the sequence is -1.5.
i.e. [tex]f(1)=-1.5[/tex]
To find the next term , we put n=1 in the given expression, we get
[tex]f(1 + 1) = -2f(1)\\\\\Rightarrrow\ f(2)=-2(-1.5)=3[/tex]
Hence, the next term in the sequence is 3.